Optimal income taxation and public good provision in a two-class economy - Felix Bierbrauer (Max Planck Institute for Research on Collective Goods, 2005)
This paper combines the problem of optimal income taxation with the free-rider problem in public good provision. There are two groups of individuals with private information on their earning ability and their valuation of a public good. Adjustments of the transfer system are needed to discourage the more productive from exaggerating the desirability of public good provision. Similarly, the less productive need to be prevented from understating their valuation. Relative to an optimal income tax, which focuses solely on earning ability, income transfers are increased whenever a public good is installed and are decreased otherwise.
Keywords: D71; D82; H21; H41; 380; Income Taxation; Public Good Provision; Revelation of Preferences; Two-dimensional Heterogeneity; Optimale Besteuerung; Einkommensteuer; Öffentliches Gut